Evaluation of chemical treatments on Echinochloa crus-galli seed dormancy and premilinary allelopathic effects of Aegiceras corniculatum macerates on its growth - Thu Hien, Khong; Truc Quynh, Bui; Van Tan, Dao (Academia Journal of Biology, 2026)
Echinochloa crus-galli is a potential species for allelopathic studies due to its characteristic advantages. However, the presence of seed dormancy impedes allelopathy research. Our laboratory study was carried out to evaluate the effects of several treatments, including gibberellic acid (GA3), 98% sulfuric acid, 1% sodium hypochlorite, and co-treatment (98% H2SO4 + GA3) on the germination and vigor indices of E. crus-galli seeds. The results indicated that there was no effect on the seed germination and growth with GA3 treatment, whereas 1% NaClO treatments was effective only with a 160-minute treatment, with a germination index of 42.50 ± 2.09, and a vigor index of 522.24 ± 23.97. The use of 98% H2SO4 prior to sowing significantly increased both parameters, with effective treatment time of 10 minutes and 20–40 minutes for seeds harvested at 12 months and 3-month respectively. These findings support the hypothesis that E. crus-galli seeds have a physical dormancy that delays germination. Furthermore, combined treatment of 98% H2SO4-GA3 25 ppm significantly enhanced seed sprouting (73.12 ± 10.64) and vitality (550.13 ± 133.93), representing the most effective dormancy-breaking method. Based on our optimized protocol findings, we further investigated the allelopathic effect of Aegiceras corniculatum macerate on E. crus-galli growth, suggesting that this mangrove species could serve as a potential donor plant for allelopathic approaches in future E. crus-galli control strategies.